2019
DOI: 10.1108/nfs-04-2018-0110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of citrus latifolia extract on dyslipidemia and tissues redox status in rats fed a high-cholesterol diet

Abstract: Purpose This study aims to investigate the possible effect of Citrus latifolia (CL) extract on biomarkers of oxidative stress, including lipid peroxidation products in rats fed a high cholesterol diet Design/methodology/approach Hypercholesterolemia was induced by feeding normocholesterolemic rats 1 per cent cholesterol-enriched diet for 15 days. An experimental group (n = 20) was divided into two groups (n = 10) and fed the same diet with or without CL lyophilized aqueous extract (1 per cent) for four weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Current study revealed the negative effects of HFD-induced obesity against vitamin D status, and therefore, the need for life style modification or diet improvements in preventing the side effects of HFD is further warranted, as previously suggested by Bensalah et al (2018). Previous studies have suggested numerous supplements for improving cardiometabolic risk factors, body weight or oxidative stress markers in animal models (Ani and Aginam, 2018;Mir et al, 2019); however, our study, for the first time, specified the role of vitamin D in improving the inflammatory status in the renal tissue and renal injury in HFDinduced vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 67%
“…Current study revealed the negative effects of HFD-induced obesity against vitamin D status, and therefore, the need for life style modification or diet improvements in preventing the side effects of HFD is further warranted, as previously suggested by Bensalah et al (2018). Previous studies have suggested numerous supplements for improving cardiometabolic risk factors, body weight or oxidative stress markers in animal models (Ani and Aginam, 2018;Mir et al, 2019); however, our study, for the first time, specified the role of vitamin D in improving the inflammatory status in the renal tissue and renal injury in HFDinduced vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 67%
“…After this design, 31 articles remained, the full texts of which were analyzed, thus yielding 27 articles that were finally included in the qualitative synthesis ( Figure 1 ; Tables 1–3 ). Of these, 22 studies were preclinical trials ( Vinson et al, 1998 ; Bok et al, 1999 ; Terpstra et al, 2002 ; Zulkhairi et al, 2010 ; Ding et al, 2012 ; Kang et al, 2012 ; Raasmaja et al, 2013 ; Lu et al, 2013 ; Kim et al, 2013 ; Muhtadi et al, 2015 ; Dinesh and Hegde, 2016 ; Shin et al, 2016 ; Ashraf et al, 2017 ; Fayek et al, 2017 ; Chou et al, 2018 ; Feksa et al, 2018 ; Mir et al, 2019 ; Sato et al, 2019 ; Hase-Tamaru et al, 2019 ; Ling et al, 2020 ; Ke et al, 2020 ; Lee et al, 2020 ), 3 were exclusively clinical studies ( Gorinstein et al, 2007 ; Toth et al, 2015 ; Cai et al, 2017 ) and 1 study contained preclinical and clinical protocols ( Mollace et al, 2011 ) ( Figure 1 ). For the quantitative synthesis, 25 articles ( Vinson et al, 1998 ; Bok et al, 1999 ; Gorinstein et al, 2007 ; Zulkhairi et al, 2010 ; Mollace et al, 2011 ; Ding et al, 2012 ; Kang et al, 2012 ; Terpstra et al, 2012; Kim et al, 2013 ; Lu et al, 2013 ; Raasmaja et al, 2013 ; Muhtadi et al, 2015 ; Dinesh and Hegde, 2016 ; Shin et al, 2016 ; Ashraf et al, 2017 ; Cai et al, 2017 ; Fayek et al, 2017 ; Chou et al, 2018 ; Feksa et al, 2018 ; Hase-Tamaru et al, 2019 ; Mir et al, 2019 ; Sato et al, 2019 ; Ke et al, 2020 ; Lee et al, 2020 ; …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 22 studies were preclinical trials ( Vinson et al, 1998 ; Bok et al, 1999 ; Terpstra et al, 2002 ; Zulkhairi et al, 2010 ; Ding et al, 2012 ; Kang et al, 2012 ; Raasmaja et al, 2013 ; Lu et al, 2013 ; Kim et al, 2013 ; Muhtadi et al, 2015 ; Dinesh and Hegde, 2016 ; Shin et al, 2016 ; Ashraf et al, 2017 ; Fayek et al, 2017 ; Chou et al, 2018 ; Feksa et al, 2018 ; Mir et al, 2019 ; Sato et al, 2019 ; Hase-Tamaru et al, 2019 ; Ling et al, 2020 ; Ke et al, 2020 ; Lee et al, 2020 ), 3 were exclusively clinical studies ( Gorinstein et al, 2007 ; Toth et al, 2015 ; Cai et al, 2017 ) and 1 study contained preclinical and clinical protocols ( Mollace et al, 2011 ) ( Figure 1 ). For the quantitative synthesis, 25 articles ( Vinson et al, 1998 ; Bok et al, 1999 ; Gorinstein et al, 2007 ; Zulkhairi et al, 2010 ; Mollace et al, 2011 ; Ding et al, 2012 ; Kang et al, 2012 ; Terpstra et al, 2012; Kim et al, 2013 ; Lu et al, 2013 ; Raasmaja et al, 2013 ; Muhtadi et al, 2015 ; Dinesh and Hegde, 2016 ; Shin et al, 2016 ; Ashraf et al, 2017 ; Cai et al, 2017 ; Fayek et al, 2017 ; Chou et al, 2018 ; Feksa et al, 2018 ; Hase-Tamaru et al, 2019 ; Mir et al, 2019 ; Sato et al, 2019 ; Ke et al, 2020 ; Lee et al, 2020 ; Ling et al, 2020 ) were selected. The level of agreement among the reviewers was 0.470, being considered as moderate.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, the model of exogenous dyslipidemia induced by oil-cholesterol mixture (cholesterol with bile acid and hypothyroidism-inducing agents) is widely used to screen natural or synthetic drugs [ 13 ]. In this study, we evaluated the effects of GANMO tablets on the changes in serum lipid levels.…”
Section: Discussionmentioning
confidence: 99%